"Both Sides Now": Articulating Textiles and Fashioned Bodies in the Works of Joni Mitchell, 1968–1976. (July 2019) - Green, Denise Nicole; Kaiser, Susan B.; Doty, Kelsie; Streck, Kyra
The singer–songwriter–artist Joni Mitchell (née Anderson, born on November 7, 1943) is recognized in the worlds of music and fashion alike for her creative influences since the late 1960s. In this article, we share the findings from a critical discourse analysis of the lyrics and album art produced by Mitchell between 1968 and 1976. We consider how she represented a philosophy of "Both Sides Now" (i.e., both/and thinking) as she articulated—in words as well as visual art—three dynamic and unresolvable contradictions that provide new insights for fashion theory: (a) domesticity and worldliness, (b) bourgeois capitalism and bohemianism, and (c) beauty and destruction. In the process of articulating ambivalences and contradictions, Mitchell reveals how cultural power relations associated with gender, sexuality, age, and class (and their intersectionalities) intervene through textiles, clothing, and fashioned bodies.